Metode Pengembangan Media Pembelajaran Model True or False Physics Fun Game Card - Sepriana Leo; Diane Noviandini; Alvama Pattiserlihun (Universitas Muhammadiyah Purworejo, 2018)
Abstract - Physics learning is still considered as learning that is less attractive to some students. Students’ lack of learning interest in physics learning makes their achievement low. The purpose of this study was to develop a learning media of True or False Physics Fun Game Card, so as to make the students interested in learning physics which could increase students' interest and learning achievement. The kind of the card game